Asian Horntail Eriotremex formosanus (Matsumura) (Insecta: Hymenoptera: Symphyta: Siricidae: Tremicinae) - You Li; Jiri Hulcr (EDIS)
Since it was introduced to North America, the Asian woodwasp has become the most common wood wasp in Florida. It is not considered an economically important pest because it only attacks dying or dead trees, but the species may someday prove to be a pest and its ecological impacts in North American forests remain unknown. This 4-page fact sheet was written by You Li and Jiri Hulcr, and published by the UF Department of Entomology and Nematology, June 2015. (Photo credit: You Li, UF/IFAS)